Odpowiedzi

2010-01-25T17:44:42+01:00
A) 6xy + 2x² - 8xy - 3x² =
6xy - 8xy = 3x²- 2x² =
- 2xy = x²

O to chodzi ? Jeśli tak to daj znać a ja pomysle nad resztą:)
2 3 2
2010-01-25T17:45:38+01:00
A ) 6xy + 2x²- 8xy- 3x² = 2xy - x²
b ) √5x + 3√5x = 4√5x
c ) 2√6x - 5√3y- √6x + 4√3y= √6x - √3y
d ) (4x-y) - (3x + 2y) = x - 3y
e ) -(-a- 5) - ( -2 -3a) -2a -1 == 6 + 2a
1 5 1
  • Użytkownik Zadane
2010-01-25T17:45:54+01:00
A ) 6xy + 2x²- 8xy- 3x²=-2xy-x²
b ) √5x + 3√5x=4√5x
c ) 2√6x - 5√3y- √6x + 4√3y=√6x-√3y
d ) (4x-y) - (3x + 2y)=4x-y - 3x + 2y=x+y
e ) -(-a- 5) - ( -2 -3a) -2a -1=a- 5 +2 -3a -2a -1=-4a-5
1 3 1